Risk of spontaneous preterm birth in IVF-conceived twin pregnancies - Saccone, Gabriele; Zullo, Fabrizio; Roman, Amanda; Ward, Andrew; Maruotti, Giuseppe; Martinelli, Pasquale; Berghella, Vincenzo (The journal of maternal-fetal & neonatal medicine, 2019)
To compare the mean transvaginal ultrasound (TVU) cervical length (CL) at midtrimester in screening for preterm birth in in vitro (IVF)-conceived twin pregnancies versus spontaneously-conceived twin pregnancies. This was a retrospective cohort study. Potential study subjects were identified at the time of a routine second trimester fetal ultrasound exam at 18 0/7 to 23 6/7-week gestation. All women with twin diamniotic pregnancies screened with a single TVU CL for this trial were included. Mean TVU CLs were compared between IVF-conceived twin pregnancies and spontaneously-conceived twin pregnancies. The relationship of TVU CL with gestational age at delivery was assessed. Incidence of short TVU CL, defined as TVU CL ≤30 mm, was also calculated in the two groups. The primary outcome was the mean of TVU CL. Distribution of CL was determined and normality was examined in both groups Results: A total of 668 women with diamniotic twin pregnancies who underwent TVU CL screening between 18 0/6 and 23 6/7 weeks were included. 158 (23.7%) were IVF-conceived pregnancies, and 510 (76.3%) were spontaneously-conceived pregnancies. No women received progesterone, pessary, or cerclage for preterm birth prevention during pregnancy. The mean TVU CL was significantly lower in the IVF-conceived group (32.2 ± 10.5 mm) compared to the spontaneously-conceived group (34.1 ± 9.1 mm) (mean difference (MD) - 1.90 mm, 95%CI -3.72 to -0.08). The incidence of TVU CL ≤30 mm was 30.4% in the IVF-conceived group and 21.6% in the spontaneously-conceived group (adjusted odds ratio (aOR) 1.59, 95%CI 1.06-2.37). IVF-conceived twins had a significantly higher risk of spontaneous preterm birth <34 weeks (32.9 versus 21.2%; aOR 1.83, 95% confidence interval (CI) 1.23-2.71) and higher rate of delivery due to spontaneous onset of labor (64.5 versus 54.9%; aOR 1.50, 95%CI 1.03-2.17). For any given TVU CL measured between 18 0-7 and 23 6/7 weeks, gestational age at delivery for IVF-conceived twins was earlier by about 1 week on average compared with spontaneously-conceived twins. The higher rate of spontaneous preterm birth in IVF-conceived twin pregnancies is predicted by lower midtrimester TVU CL, as well as by the lower gestational age at birth per any given CL in the IVF-conceived compared to the spontaneously-conceived twin pregnancies.